Need Analysis for Podcast Development in Teaching Speaking for English Department Students - Helfany Amsa; Nofriza Efendi; Sherly Franschisca (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This research focuses on developing podcasts in teaching speaking which is done through needs analysis. This research is the initial stage of the ADDIE model research development, namely the needs analysis stage. Stages of needs analysis is done by survey method which is done by interview and distributing questionnaires. Interviews and questionnaires were used as data collection techniques. Interviews were conducted to dig deeper into information related to students' difficulties in interacting in speaking classes and to analyze needs for podcast development. Questionnaires were used to obtain quantitative data regarding students' needs for podcast development.